Prognostic Factors Associated with 5-Year Overall Survival in Cervical Cancer Patients Treated with Radical Hysterectomy Followed by Adjuvant Concurrent Chemoradiation Therapy at a Tertiary Care Center in Eastern Europe - Mihai Stanca; Mihai Emil Căpîlna (Diagnostics, 2021)
Background: This retrospective observational study aims to assess the 5-year overall survival and the prognostic significance of risk factors of patients who underwent radical hysterectomy followed by adjuvant concurrent chemoradiation therapy (CCRT) for FIGO stage IB1-IIB cervical cancer in a tertiary care center in Eastern Europe. Methods: From January 2010 to February 2019, 222 patients with stage IB1-IIB cervical cancer were treated with radical hysterectomy followed by adjuvant CCRT in our institution. The baseline information consisting of demographic and clinicopathologic data, treatment choices, recurrences, and outcome information was collected and examined. The survival rates were illustrated using Kaplan–Meier curves and prognosis analyses were accomplished using Cox multivariate analyses. Results: The 222 participants had a mean age of 51.2 years (28–76). The median follow-up time was 65.5 months (3–128). Tumor characteristics revealed FIGO stage (IB1 2.3%, IB2 35.1%, IB3 16.7%, IIA1 9%, IIA2 8.6%, IIB 28.4%) and the most encountered histologic cell type was squamous cell carcinoma (80.06%) followed by adenocarcinoma (11.3%). At the time of examination, 157 patients (70.07%) were alive, of which 135 (61%) were alive free of disease and 22 (9%) were alive with disease. The multivariate Cox regression analysis acknowledged stage IIB, parametrial involvement, and the presence of lymph node metastases as independent prognostic risk factors, significantly worsening the oncologic outcomes influencing the survival with a P-value of 0.076, 0.0001, and 0.008, respectively. The 5-year overall survival was 69.9%. Conclusions: Altogether, the study enhances the significance of prognostic risk factors on the 5-year overall survival of patients who underwent radical hysterectomy followed by adjuvant CCRT for FIGO stages IB1-IIB cervical cancer, allowing comparisons with other regions.